Roles of Bronchopulmonary C-fibers in airway Hyperresponsiveness and airway remodeling induced by house dust mite - Zhimei Yang; Jianguo Zhuang; Lei Zhao; Xiuping Gao; Zhengxiu Luo; Enmei Liu; Fadi Xu; Zhou Fu (Respiratory Research, 2017)
Abstract Background Asthma is characterized by chronic airway inflammation, airway hyperresponsiveness (AHR), and airway remodeling. While exposure of house dust mites (HDM) is a common cause of asthma, the pathogenesis of the HDM-induced asthma is not fully understood. Bronchopulmonary C-fibers (PCFs) contribute to the neurogenic inflammation, viral infection induced-persistent AHR, and ovalbumin induced collagen deposition largely via releasing neuropeptides, such as substance P (SP). However, PCF roles in the pathogenesis of the HDM-induced asthma remain unexplored. The goal of this study was to determine what role PCFs played in generating these characteristics. Methods We compared the following variables among the PCF-intact and -degenerated BALB/c mice with and without chronic HDM exposure (four groups): 1) AHR and pulmonary SP; 2) airway smooth muscle (ASM) mass; 3) pulmonary inflammatory cells; and 4) epithelium thickening and mucus secretion. Results We found that HDM evoked AHR associated with upregulation of pulmonary SP and inflammation, ASM mass increase, epithelium thickenings, and mucus hypersecretion. PCF degeneration decreased the HDM-induced changes in AHR, pulmonary SP and inflammation, and ASM mass, but failed to significantly affect the epithelium thickening and mucus hypersecretion. Conclusion Our data suggest an involvement of PCFs in the mechanisms by which HDM induces allergic asthma via airway inflammation, AHR, and airway remodeling.